The V-ATPase as a Target for Antifungal Drugs - Zhang, Yongqiang; Rao, Rajini (Current Protein and Peptide Science, 2012)
The ubiquitous and essential V-ATPase is a worthy chemotherapeutic target in the escalating battle against invasive fungal infections. Pathogenic fungi require optimum V-ATPase function for secretion of virulence factors, induction of stress response pathways, hyphal morphology and homeostasis of pH and other cations in order to successfully survive within and colonize the host. This review discusses why impairment of V-ATPase activity confers multidrug sensitivity and loss of virulence. Recent evidence points to the V-ATPase as a novel downstream target of the azole class of antifungals that inhibit the biogenesis of ergosterol. Depletion of ergosterol from vacuolar membranes led to progressive alkalization of yeast vacuoles, loss of V-ATPase activity and growth inhibition that could be rescued by exogenous ergosterol feeding. Other studies point to a critical role for sphingolipids, phospholipids and cardiolipin in V-ATPase function. Thus, drugs that inhibit the V-ATPase directly, or indirectly by modulating the membrane milieu, can profoundly affect fungal viability and virulence. These findings justify a systematic screen for fungal specific V-ATPase inhibitors or membrane active compounds that can be used in antifungal chemotherapy.
Keywords: Mucosal